Firm size does matter: New evidence on the determinants of cash holdings - Efstathios Magerakis; Konstantinos Gkillas Gillas; Athanasios Tsagkanos; Costas Siriopoulos (Journal of Risk and Financial Management, 2020)
We study the financial determinants of cash holdings and discuss the importance of firm size in the post-crisis period. We employ panel data regression analysis on a sample of 6629 non-financial and non-utility listed companies in the United Kingdom from 2010 to 2018. We focus on the comparative analysis of large, medium, and small size firms in terms of cash holdings. Our findings indicate that cash levels are higher for firms with riskier cash flows, more growth opportunities, and higher R&D expenditures. In contrast, the firms' cash holdings decrease when the substitutes of cash, cash flows, and capital expenditures increase. We show that small-sized firms tend to hold more cash than their larger counterparts due to precautionary motives. Further, we confirm a significant and varying association between managerial ownership and cash holdings. The study is robust to different regression specifications, additional analyses, and endogeneity tests. Overall, we add to the prior literature by identifying the effect of firm-level attributes and governance characteristics on cash policy during the post-crisis period. To the best of the authors' knowledge, this is the first work that provides insights on the way that firm characteristics impact cash holdings, considering the differences among firm size groupings.
Keywords: G30; G32; M41; 330; agency costs; board size; cash holdings; corporate governance; firm size; pecking order theory; speed of adjustment; the UK; trade-off model